Addressing muslim transgenders' health issues using religious approach in the Malaysian setting - Suofeiya M.; Razali Z.A.; Subri I.M.; Draman S.; Isa M.L.M.; Ibrahim M.B.; Mokhtar R.H. (American Scientific Publishers, 2024)
Indexed by SCOPUS